2020
DOI: 10.1038/s41598-020-71616-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response of the Siberian wood frog Rana amurensis to extreme hypoxia

Abstract: the Siberian wood frog Rana amurensis is a recently discovered example of extreme hypoxia tolerance that is able to survive several months without oxygen. We studied metabolomic profiles of heart and liver of R. amurensis exposed to 17 days of extreme hypoxia. Without oxygen, the studied tissues experience considerable stress with a drastic decrease of ATP, phosphocreatine, and NAD+ concentrations, and concomitant increase of AMP, creatine, and NADH. Heart and liver switch to different pathways of glycolysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Additionally, alanine may be transported to the liver, where it has been suggested to act as a precursor to gluconeogenesis [ 58 , 60 ]. Interestingly, large alanine accumulation in liver tissue has also been seen in the Siberian wood frog Rana amurensis during extreme hypoxia [ 61 ], indicating that alanine may be part of a common mechanism for anoxia-tolerant as well as hypoxia-tolerant species. This additional source of energy would potentially reduce the rate of glycolysis and in this way conserve glucose, which would benefit the crucian carp greatly during prolonged anoxia exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alanine may be transported to the liver, where it has been suggested to act as a precursor to gluconeogenesis [ 58 , 60 ]. Interestingly, large alanine accumulation in liver tissue has also been seen in the Siberian wood frog Rana amurensis during extreme hypoxia [ 61 ], indicating that alanine may be part of a common mechanism for anoxia-tolerant as well as hypoxia-tolerant species. This additional source of energy would potentially reduce the rate of glycolysis and in this way conserve glucose, which would benefit the crucian carp greatly during prolonged anoxia exposures.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism represents a response to hypoxia based on a coordinate slowdown of both ATP production and consumption to save energy and diminish ROS and other toxic end-products accumulation. Quite recently, the ability to maintain low succinate levels during extreme hypoxic conditions was associated to hypoxia tolerance in amphibians and reptile vertebrates 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in apparent contrast to hypoxia in the Siberian wood frog R. amurensis. A study using the same methods [14] revealed reduced ATP/ADP ratio but no products of nucleotide degradation in response to aqueous hypoxia in this species, and the levels of GPC and choline were mostly reduced, not elevated. It looks like that the observed changes are well tolerated, since −8 • C is far from critical for S. keyserlingii.…”
Section: Markers Of Stressmentioning
confidence: 62%
“…In vertebrates, suppression of oxidative phosphorylation is believed to result in the accumulation of high quantities of succinate, which is caused by the reversal of the activity of succinate dehydrogenase in the absence of oxygen [41]. Accumulation of succinate under hypoxia was detected in the Siberian wood frog Rana amurensis [14], the crucian carp Carassius carassius [42], and the red-eared slider turtle Trachemys scripta [43]. Surprisingly, we found no changes in succinate level in the liver, while in the muscle its average concentrations even decrease approximately twofold (Figure 4B).…”
Section: Freezing Bioenergeticsmentioning
confidence: 99%
See 1 more Smart Citation